Assessment of predisposition in the acquisition of the english language and motor development in children with autism spectrum disorder: Case report - Bernardo de Carvalho, Fernanda; Batista Saldanha, Jackeline; Protestato, Fernanda; Mendes Trevizan Silva, Mariana; Lima Silva, Giovana; Benite Palma Lopes, Jamile; Barbosa Cordeiro, Lorraine; Santos Oliveira, Claudia (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Autism Spectrum Disorder (ASD) is a complex neurobiological disorder. Characterized by language deficits, however, it is known that there is a development of bilingualism in the autistic population. Delay in motor development is present in the population, with deficits in fine and gross motor coordination. Objective: The present study aims to evaluate the predisposition to acquire a second language and motor development in children with ASD. Method: The case report is composed of four children, verbal with the cognitive and physical capacity to participate in the evaluations. Mean age ± 8 years and 3 months, 50% male, 100% literate. Distributed into two groups: group I: two children diagnosed with ASD according to DSM-V and group II: two children with typical development. The group of children with ASD underwent the assessment protocol consisting of the application of the Childhood Autism Rating Scale (CARS) while the Revised Psychoeducational Profile (PEP-R) and the Placement Test were applied in both groups. Result: Children with ASD assessed with CARS had a low level of support. Regarding the PEP-R, the same group showed a deficit in the development of fine and gross motor coordination compared to group II. The child with ASD from the public network had a lower score compared to the child from the private network in relation to the level of development of bilingualism, both in reading and writing. Conclusion: It is possible to suggest that the development of fine and gross motor skills of children with ASD are deficient, however, they demonstrated a good result in the predisposition to learning a second language, including the child who studies in a public school. Although its development is a little smaller.